Evaluation and Prevention of Mycotoxin Contamination and Toxicological Effects (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Over the last few decades, mycotoxins, toxic fungal secondary metabolites that frequently contaminate foods and feeds, have attracted great interest at both scientific and industrial levels. The toxicity of these compounds has led to several regulations in many countries to control and quantify these contaminants for their subsequent risk assessment. Many analytical methods have been developed, from rapid screening tests to mass spectrometry technology and the establishment of multi-mycotoxin-validated methods. At present, the food processing industry is looking for technologies to remove or reduce mycotoxins from food materials, with the aim of maintaining the nutritive value and palatability of the products treated. New non-destructive strategies, also known as innovative non-thermal food processing technologies, are being explored as an alternative to conventional thermal treatments for mycotoxin decontamination. The aim of the Special Issue “Evaluation and Prevention of Mycotoxin Contamination and Toxicological Effects” was to provide a space of exchange to address analytical methodology for mycotoxin determination for subsequent risk assessment as well as the identification of toxicological effects and the prevention of contamination. More specifically, the Special Issue covers two main aspects: experimental data and literature reviews. The methodology covered molecular methods for mycotoxin assessment to high-throughput mass spectrometry techniques with the inclusion of emerging mycotoxins in occurrence data and the use of computational methods in mycotoxin risk assessment.